Correlation between nutritional adequacy, Fe content, body fat percentage, and muscle mass percentage with physical fitness - Sonya Hayu Indraswari; Mohammad Zen Rahfiludin; Ali Rosidi (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2022)
This study aims to determine the correlation between nutritional adequacy, Fe content, body fat percentage, and muscle mass percentage with physical fitness in football athletes. Adequacy of nutrients (energy, protein, fat, protein and Fe) was obtained with a 2×24 hour recall. The Fe content value of Fe was measured using the cyanmethemoglobin method and sTfR was measured using the ELWASA method. The percentage of fat and muscle was obtained by using a Bioelectrical Impedance Analysis tool. Physical fitness was measured using the ACSPFT (Asian Committee on Standardization of Physical Fitness Test) test which includes long jumps, pull-ups, sit-ups, sprints or sprints, shuttle run tests, sit and reach and long runs. The bivariate statwastical test used was the Pearson and Rank-Spearman correlation test, while the multivariate test used the Linear Regression test. There was a correlation between carbohydrate adequacy and physical fitness (p = 0.008). Physical fitness related to carbohydrate adequacy was agility and hand muscle strength (shuttle run and pull-up). There was no correlation between adequacy of energy, protein, fat, Fe Content, fat percentage, muscle percentage and physical fitness of athletes. The results of multivariate analysis showed that the most influential on physical fitness was fat adequacy (Rsquwere=14,6%).